Prenatal nursing care: Experience report (Research, Society and Development, 2021)
Objective: Prenatal care is a health care for pregnant women, and it becomes a powerful strategy to reduce maternal and neonatal mortality. In this sense, the study will describe the experience lived as a nursing student, given the role of nurses in care to pregnant women at the basic health unit in a municipality in the interior of Bahia. Method: This is a descriptive study of an experience report type about the experience in the Supervised Internship, on the role of nurses during prenatal care in the city of Irecê-BA. Results: In this sense, it was possible to observe the role of nurses in low-risk prenatal consultations. Where anamnesis and physical examination were carried out during the consultations, in addition to the prescription and interpretation of exams, prescription of medications, health education through general guidance on pregnancy, the consultations were alternated between the nurse and the doctor. Assistance was provided in a humane way, providing early detection of possible problems that may occur during pregnancy. Conclusion: It is necessary to pay attention to the prenatal consultation in a complete way due to the wide range of information to be recorded in various forms that involve this consultation.